Transplanted Human Induced Pluripotent Stem Cell-Derived Neural Progenitor Cells Do Not Promote Functional Recovery of Pharmacologically Immunosuppressed Mice with Contusion Spinal Cord Injury. Issue 9 (September 2015) - Pomeshchik, Yuriy; Puttonen, Katja A.; Kidin, Iurii; Ruponen, Marika; Lehtonen, Sarka; Malm, Tarja; Åkesson, Elisabet; Hovatta, Outi; Koistinaho, Jari
Improved functional recovery after spinal cord injury by transplantation of induced pluripotent stem cell-derived neural stem/progenitor cells (iPSC-NPCs) has been reported. However, beneficial effects of iPSC-based therapy have so far been produced mostly using genetically immunodeficient rodents. Because of the long time required for generation and characterization of iPSCs, the use of autologous iPSCs for treating patients with acute spinal cord injury (SCI) is not feasible. Therefore, it is of utmost importance to investigate the effect of iPSC-based therapy on functional recovery after SCI using pharmacologically immunosuppressed, immunocompetent animal models. Here we studied the functional outcome following subacute transplantation of human iPSC-derived NPCs into contused mouse spinal cord when tacrolimus was used as an immunosuppressive agent. We show that human iPSC-derived NPCs transplanted into pharmacologically immunosuppressed C57BL/6J mice exhibited poor long-term survival and failed to improve functional recovery after SCI as measured by Basso Mouse Scale (BMS) for locomotion and CatWalk gait analysis when compared to vehicle-treated animals. The scarce effect of iPSC-based therapy observed in the current study may be attributable to insufficient immunosuppressive effect, provided by monotherapy with tacrolimus in combination with immunogenicity of transplanted cells and complex microenvironment of the injured spinal cord. Our results highlight the importance of extensive preclinical studies of transplanted cells before the clinical application of iPSC-based cell therapy is achieved.